STUDY OF YEAST QUALITY ENHANCEMENT BY FORAGE DEPROTEINISED JUICE (DPJ) FERMENTATION - Jadhav, Rajesh K.; Deshmukh, Sayali (Journal of Experimental Sciences)
Process of green crop fractionation (GCF) was considered and its byproducts were tested for evaluation. The byproducts obtained were pulp, LPC (Leaf protein concentrate), Juice, Deproteinised juice and pressed crop (PC). The dry weight of LPC from each crop was measured. Maize forage LPC was more as compared with other forages. Deproteinised Juice (DPJ) is utilised as a medium for the fermentation of yeast. This yeast growth was compared with the yeast grown on Hansens broth media as control. Various concentration ratios of DPJ and Hansens media were prepared and yeast was fermented. Yeast mycelia grown on DPJ was found higher as compared with other concentrations. The culture filtrates of yeast mycelia collected and used to study the enzyme invertase by immobilisation method and the presence of alcohol was by iodoform test. Almost all the samples of various concentrations showed the presence of alcohol by proper secretion of enzyme zymase. Enzyme invertase appropriately found less in the culture filtrate of yeast mycelia grown on DPJ alone. Therefore DPJ is responsible for less breakdown of sucrose as compared with Hansens media which breaks down more sucrose into glucose and fructose by the enzyme invertase.